Global-local ansatz and dynamical coherent potential approximation study of off-diagonal exciton-phonon coupling - Liu, Qingmei (2011)
We study the generalized Holstein Hamiltonian in the simultaneous presence of diagonal and off-diagonal exciton-phonon couplings using the global-local Ansatz and the dynamical coherent potential approximation (under the Hartree approximation). The former yields detailed exciton-phonon correlations for polaron states in the lowest polaron energy band in addition to the state-of-the-art ground-state wave functions, while the latter reveals polaron dynamic information in the form of extended energy spectra and spectral density functions. Lowest polaron energy bands generated by the two methods are compared.